How does reward compete with goal-directed and stimulus-driven shifts of attention?. Issue 1 (2nd January 2017) - Bourgeois, Alexia; Neveu, Rémi; Bayle, Dimitri J.; Vuilleumier, Patrik
ABSTRACT: In order to behave adaptively, attention can be directed in space either voluntarily (i.e. endogenously) according to strategic goals, or involuntarily (i.e. exogenously) through reflexive capture by salient or novel events. The emotional or motivational values of stimuli can also influence attentional orienting. However, little is known about how reward-related effects compete or interact with endogenous and exogenous attention mechanisms. Here we designed a visual search paradigm in which goal-driven and stimulus-driven shifts of attention were manipulated by classic spatial cueing procedures, while an irrelevant, but previously rewarded stimulus also appeared as a distractor and hence competed with both types of spatial attention during search. Our results demonstrated that stimuli previously associated with a high monetary reward received higher attentional priority in the subsequent visual search task, even though these stimuli and reward were no longer task-relevant, mitigating the attentional orienting induced by both endogenous and exogenous cues.